(untitled) (RIAF. International Journal of Physical Activity, 2024)
Autism Spectrum Disorder (ASD) is an issue that affects many children worldwide. Currently, it is recognized that ASD not only impacts this group but can also persist into adulthood. This work focuses on the use of playful techniques to promote psychomotor development in children aged 4-5 years diagnosed with Autism Spectrum Disorder, with the main goal of improving their overall development. The methodology employed involved a descriptive field study, supported by a detailed literature review to justify the proposal. Surveys were conducted with teachers, interviews with the institution’s director, and specific observations of children diagnosed with this disorder. The findings showed a positive attitude from the teachers towards the playful strategy and highlighted progress in the social integration and psychomotor development of the children, including involving their parents in the process. The conclusions indicate the feasibility and importance of implementing a playful strategy that fosters the motor aspect in the study subjects, emphasizing the need for multidisciplinary approaches to maximize the development of children with ASD.